Malignant Hyperthermia in PICU-From Diagnosis to Treatment in the Light of Up-to-Date Knowledge - Martina Klincová; Dagmar Štěpánková; Ivana Schröderová; Eva Klabusayová; Petr Štourač (MDPI AG, 2022)
Malignant Hyperthermia (MH) is a rare, hereditary, life-threatening disease triggered by volatile anesthetics and succinylcholine. Rarely, MH can occur after non-pharmacological triggers too. MH was detected more often in children and young adults, which makes this topic very important for every pediatric specialist, both anesthesiologists and intensivists. MH crisis is a life-threatening severe hypermetabolic whole-body reaction. Triggers of MH are used in pediatric intensive care unit (PICU) as well, volatile anesthetics in difficult sedation, status asthmaticus or epilepticus, and succinylcholine still sometimes in airway management. Recrudescence or delayed onset of MH crisis hours after anesthesia was previously described. MH can also be a cause of rhabdomyolysis and hyperpyrexia in the PICU. In addition, patients with neuromuscular diseases are often admitted to PICU and they might be at risk for MH. The most typical symptoms of MH are hypercapnia, tachycardia, hyperthermia, and muscle rigidity. Thinking of the MH as the possible cause of deterioration of a patient's clinical condition is the key to early diagnosis and treatment. The sooner the correct treatment is commenced, the better patient´s outcome. This narrative review article aims to summarize current knowledge and guidelines about recognition, treatment, and further management of MH in PICU.